2012
DOI: 10.1371/journal.pone.0031391
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Th1 Lymphocytes Is Regulated by CD152 (CTLA-4)-Mediated Signaling via PI3 Kinase-Dependent Akt Activation

Abstract: Efficient adaptive immune responses require the localization of T lymphocytes in secondary lymphoid organs and inflamed tissues. To achieve correct localization of T lymphocytes, the migration of these cells is initiated and directed by adhesion molecules and chemokines. It has recently been shown that the inhibitory surface molecule CD152 (CTLA-4) initiates Th cell migration, but the molecular mechanism underlying this effect remains to be elucidated. Using CD4 T lymphocytes derived from OVA-specific TCR tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Additionally, CTLA4 ligation was found to regulate distal signalling events by inhibiting ERK and JNK phosphorylation 48 . Interestingly, the YVKM motif also binds PI3K, and it has recently been demonstrated that CTLA4 promotes CD4 + T cell migration through PI3K-dependent AKT activation 49 . Meanwhile, it remains unclear whether the CTLA4–PI3K–AKT pathway also has a co-stimulatory function.…”
Section: Molecular Pathway Of T Cell Co-signallingmentioning
confidence: 99%
“…Additionally, CTLA4 ligation was found to regulate distal signalling events by inhibiting ERK and JNK phosphorylation 48 . Interestingly, the YVKM motif also binds PI3K, and it has recently been demonstrated that CTLA4 promotes CD4 + T cell migration through PI3K-dependent AKT activation 49 . Meanwhile, it remains unclear whether the CTLA4–PI3K–AKT pathway also has a co-stimulatory function.…”
Section: Molecular Pathway Of T Cell Co-signallingmentioning
confidence: 99%
“…We have shown so far that in the CTLA-4-mediated modulation of T-cell functions, such as proliferation and cytokine production [3,4,18,20] , but also in connection with activation-induced cell death (a form of apoptosis), CTLA-4 signals interfere differentially with gene expression by inhibiting the activation of key transcription factors such as NFAT, eomesodermin, GATA3, and FKHRL1 (but not cKrox, AP1, or T-bet!). In particular, we have been able to show that CTLA-4 induces the expression of Bcl-2 and of the chemokine receptor CCR5, and activates the enzyme activity of PI3 kinase [10,11,24] .…”
Section: Ctla-4 Induces Specific Migration Of Th1 Lymphocytesmentioning
confidence: 95%
“…This ensures that the immune response is stopped. In addition, T-lymphocytes that receive a CTLA-4 signal migrate along inflammatory and homeostatic chemokine gradients [23,11] . The lymphocytes surviving at the end of an immune response and migrating to memory areas might be potential precursors of memory cells.…”
Section: Ctla-4 In the Differentiation Of T-lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations